Two cases of retinal vasculitis in ocular tuberculosis involving different parts of the vascular system - Kok, Howe Sen; Tara Mary George,; Mae-Lynn Catherine Bastion,; Muhaya Hj Mohamad, (Penerbit UKM, 2006)
Two case reports of retinal vasculitis in presumptive ocular tuberculosis are presented. Case 1 is a 26-year-old Malay woman who had phlebitis with choroidal lesions and case 2 is a 27 year old Malay woman who had occlusive arteritis. Both subjects had positive Mantoux tests with negative systemic screen. Both responded clinically to anti-tuberculous therapy within days of commencing therapy. There was however concurrent increase in vitritis which decreased following anti-inflammatory doses of oral corticosteroids. These two cases represent a rare mode of presentation of ocular tuberculosis for which a high index of suspicion is needed. Multidrug anti-tuberculous therapy should be combined with oral corticosteroids for effective treatment